Using CBI in ESP: The role of explicit instruction - Shirav, Anastasia (International Journal of Language and Literary Studies, 2023)
The current paper investigated the results of year-long teaching of a journalistic genre implicitly using a CBI-based syllabus. The participants were 20 Japanese learners of English at a vocational college in Japan. The feature articles written by the students at the end of the school year were compared to those provided as high-quality examples. The data were analyzed qualitatively. The two corpora were compared regarding genre-specific moves and lexical bundles used. The results indicated that the lack of explicit ESP-related instruction led to the inability of the participants to produce a feature article. They also supported a cognitive apprenticeship approach to raise learners’ awareness of the learning process. In addition, the results suggested that using CBI in ESP can be beneficial when integrated with ESP-specific methods.